Redundant Memory Mappings for Fast Access to Large Memories - Karakostas, Vasileios; Gandhi, Jayneel; Ayar, Furkan; Cristal, Adrián; Hill, Mark D.; McKinley, Kathryn S; Nemirovsky, Mario; Swift, Michael M.; Ünsal, Osman (ACM/IEEE International Symposium on Computer Architecture (ISCA), 2015)
Page-based virtual memory improves programmer productivity, security, and memory utilization, but incurs performance overheads due to costly page table walks after TLB misses. This overhead can reach 50% for modern workloads that access increasingly vast memory with stagnating TLB sizes. To reduce the overhead of virtual memory, this paper proposes Redundant Memory Mappings (RMM), which leverage ranges of pages and provides an efficient, alternative representation of many virtual-to-physical mappings. We define a range be a subset of process’s pages that are virtually and physically contiguous. RMM translates each range with a single range table entry, enabling a modest number of entries to translate most of the process’s address space. RMM operates in parallel with standard paging and uses a software range table and hardware range TLB with arbitrarily large reach. We modify the operating system to automatically detect ranges and to increase their likelihood with eager page allocation. RMM is thus transparent to applications. We prototype RMM software in Linux and emulate the hardware. RMM performs substantially better than paging alone and huge pages, and improves a wider variety of workloads than direct segments (one range per program), reducing the overhead of virtual memory to less than 1% on average.